2003
DOI: 10.1034/j.1600-0706.2003.11912.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony in brown trout, Salmo trutta, population dynamics: a ‘Moran effect’ on early‐life stages

Abstract: N. 2003. Synchrony in brown trout, Salmo trutta, population dynamics: a 'Moran effect' on early-life stages. -Oikos 100: 43-54.Synchrony among populations (i.e. spatial covariation in temporal fluctuations of population size or growth rate) is a common feature to many animals. Both large-scale autocorrelated climatic factors (the 'Moran effect') and dispersal between populations are candidates to explain synchrony, although their relative influence is difficult to assess. Only a few investigations have reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
107
3
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(124 citation statements)
references
References 54 publications
12
107
3
2
Order By: Relevance
“…Once age-class strength was determined, densities of several subsequent age-classes could be predicted with reasonable accuracy. Hydrologic influences on brown trout year-class strength have been observed mostly in high-gradient, mountainous streams in the United States and Europe (e.g., Strange et al 1992;Nehring and Anderson 1993;Spina 2001;Cattanéo et al 2002Cattanéo et al , 2003Lobón-Cerviá 2004;Lobón-Cerviá and Rincón 2004). Aside from our study and Nuhfer et al's (1994) study on the South Branch Au Sable River, such relationships have not been noted for low-gradient trout streams in glaciated Midwestern states.…”
Section: Regional Influences On Population Dynamicssupporting
confidence: 52%
“…Once age-class strength was determined, densities of several subsequent age-classes could be predicted with reasonable accuracy. Hydrologic influences on brown trout year-class strength have been observed mostly in high-gradient, mountainous streams in the United States and Europe (e.g., Strange et al 1992;Nehring and Anderson 1993;Spina 2001;Cattanéo et al 2002Cattanéo et al , 2003Lobón-Cerviá 2004;Lobón-Cerviá and Rincón 2004). Aside from our study and Nuhfer et al's (1994) study on the South Branch Au Sable River, such relationships have not been noted for low-gradient trout streams in glaciated Midwestern states.…”
Section: Regional Influences On Population Dynamicssupporting
confidence: 52%
“…Hydrologic influences on brown trout year-class strength have been observed previously in Michigan (Nuhfer et al 1994) as well as in other states and European countries (e.g., Strange et al 1992;Cattanéo et al 2002Cattanéo et al , 2003Lobón-Cerviá 2004;Lobón-Cerviá and Rincón 2004). Nehring and Anderson (1993) found that variable recruitment of age-0 brown trout and rainbow trout Oncorhynchus mykiss in 10 Colorado streams over a 13-year period was largely attributable to variation in mean monthly discharge Spina (2001) observed an inverse relationship between peak discharge during incubation and density of age-0 brown trout in a highgradient California stream, along with carryover of relative year-class strength to older age-groups.…”
Section: Synchrony Of Trout Population Dynamicsmentioning
confidence: 58%
“…Spatial synchrony in population dynamics (Kendall et al 2000;Engen et al 2002) has been reported for a wide variety of animal species including insects (Hanski & Woiwod 1993;Williams & Liebhold 2000;Bjornstad et al 2002;Peltonen et al 2002), feral sheep on islands (Grenfell et al 1998), Svalbard reindeer (Aanes et al 2003), caribou and musk oxen (Post & Forchhammer 2002), muskrat and mink across Canada (Haydon et al 2001), grouse in Italy (Cattadori et al 2000), freshwater fishes (Cattaneo et al 2003), sea turtles (Chaloupka 2001) and diseases in towns (Bolker & Grenfell 1996). Regionally correlated climatic factors like rainfall, drought or extremes of winter temperature are also postulated as causing large-scale synchrony in the fluctuations of populations of short-lived plants (Hopkins 1978;Dunnett et al 1998;Coomes et al 2002) and synchronized time of flowering in several plant species over distances of up to 500 km (Post 2003).…”
Section: Introductionmentioning
confidence: 98%